2012
DOI: 10.1002/eji.201242396
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infection augments NOD2 signaling in an IFN‐β‐dependent manner in human primary cells

Abstract: Respiratory syncytial virus (RSV) is a major cause of lower respiratory tract infections in infants, with remarkable variability in disease severity. An exaggerated proinflammatory response and influx of leukocytes is part of the pathogenesis of severe RSV disease. Here, we show an increase in proinflammatory cytokine production by human immune cells after stimulation with RSV and muramyl dipeptide (MDP), which is recognized by nucleotide‐binding oligomerization domain containing 2 (NOD2). PBMCs from Crohn's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…Where relevant, PR8/34 was purified by rate zonal sedimentation on 25-80% w/v sucrose gradients as described [15]. Green fluorescent protein (GFP)-labeled RSV A2 (rgRSV30) [16] was cultured on HeLa cells as described previously [17]. Virus concentration was determined by titration on HeLa cells.…”
Section: Methodsmentioning
confidence: 99%
“…Where relevant, PR8/34 was purified by rate zonal sedimentation on 25-80% w/v sucrose gradients as described [15]. Green fluorescent protein (GFP)-labeled RSV A2 (rgRSV30) [16] was cultured on HeLa cells as described previously [17]. Virus concentration was determined by titration on HeLa cells.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, recent studies have revealed a synergistic proinflammatory cytokine response in human PBMCs stimulated with RSV followed by MDP stimulation. Interestingly, this synergic response is absent in PBMCs isolated from CD patients homozygous for the 3020insC mutation in the NOD2 gene [133]. These results suggest a critical role of NOD2 in this synergy and add an interesting aspect in how the loss of function mutations in NOD2 can eliminate essential immune responses.…”
Section: Cross-talk Between Nod2 and Other Innate Pathwaysmentioning
confidence: 77%
“…In a previous study we showed that this model system can very easily be adapted to study inflammatory pathways induced by other viruses, e.g. influenza or rhinovirus 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as an addition to the cell lines and animal models currently used, we propose to use human primary PBMCs as a model for stimulation with HRSV. Human PBMCs can be obtained from a range of individuals to address specific research questions, including young children 6 , immunocompromised individuals as well as healthy adults 7 or elderly individuals 8 . PBMCs can be used to study innate aspects of infection as well as the adaptive response to the virus.…”
Section: Introductionmentioning
confidence: 99%